2008
DOI: 10.2166/wh.2008.033
|View full text |Cite
|
Sign up to set email alerts
|

Drinking-water safety – challenges for community-managed systems

Abstract: A targeted review of documented waterborne disease outbreaks over the past decades reveals some recurring themes that should be understood by drinking-water suppliers.Evidence indicates the outbreaks are often linked to some significant change in conditions that provides a sudden challenge to a water system. Severe weather events, such as heavy rainfall or runoff from snow melt, as well as treatment process and system changes, are common risk factors for drinking-water outbreaks. Failure to recognise warning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
(14 reference statements)
0
17
0
1
Order By: Relevance
“…Small systems across North America are being encouraged to regionalize water supplies as a means of creating the economies of scale necessary to provide a supply of safe drinking water, maintain infrastructure, and ensure the sustainability of a region through a reliable drinking water system (Miller & Hamilton, 1988;Haque et al, 1999;Rizak & Hrudey, 2008;Langford et al, 2012;Hansen, 2013). Three systems included in this study followed a regionalization approach: the Aspen Regional Water Services Commission (AB), the Springford and Otterville drinking water system (ON), and the Donkin/Glace Bay (NS) water supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small systems across North America are being encouraged to regionalize water supplies as a means of creating the economies of scale necessary to provide a supply of safe drinking water, maintain infrastructure, and ensure the sustainability of a region through a reliable drinking water system (Miller & Hamilton, 1988;Haque et al, 1999;Rizak & Hrudey, 2008;Langford et al, 2012;Hansen, 2013). Three systems included in this study followed a regionalization approach: the Aspen Regional Water Services Commission (AB), the Springford and Otterville drinking water system (ON), and the Donkin/Glace Bay (NS) water supply.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges include the capacity to evaluate and maintain drinking water systems, secure the funds necessary to make necessary upgrades, and manage the increasingly sophisticated technical systems required to achieve new and emerging regulations (Kot et al, 2011;Haider et al, 2014;Forrer et al, 2013;Regnier, 2014). As a result, these systems are at a higher risk of providing consumers with unsafe drinking water (Eggertson, 2008;Bakker & Cook, 2011;Moffat & Struck, 2011), and often struggle to meet the rising expectations of regulators (Rizak & Hrudey, 2008;Roberson, 2011;Kot et al, 2011) and of consumers (Chapelle et al, 2009). As more than 80 per cent of drinking water systems in Canada are small (Wilson et al, 2009), addressing challenges within this cohort can yield a significant, positive impact on public health across the country.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that heavy rainfall events can significantly increase surface runoff of Cryptosporidium oocysts over agricultural land (Davies et al, ; Davies‐Colley et al, ; Lal et al, ; Tryland et al, ). Humans can then be exposed to waterborne zoonotic pathogens through recreational contact with waterways or through the consumption of contaminated drinking water (Bridgman et al, ; Cavirani, ; Hoxie et al, ; McDaniel et al, ; Rizak & Hrudey, ).…”
Section: Environmental Health Impactsmentioning
confidence: 99%
“…Precipitation-driven sediment transport can also be important in governing the mobility and loading of sediment-adsorbed microorganisms (Kim . Many waterborne disease outbreaks have been shown to be associated with heavy rainfall (Figure 8) (Curriero et al 2001;Kistemann et al 2002;WHO 2003;Rizak and Hrudey 2008;Cann et al 2013) and elevated turbidity (Morris et al 1996;Schwartz et al 1997;Abia et al 2016). For example, Curriero et al (2001) analyzed 548 waterborne disease outbreaks that occurred in the U.S. between 1948 and 1994 and found that over half of them were preceded by heavy rainfall.…”
Section: Pathogensmentioning
confidence: 99%